The influence of parenting styles and parents' mindfulness practices on adolescent emotional maturity behavior - Yeti Purnamasari Lukito; Suherman Suherman (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2021)
Emotional maturity can be obtained through parenting and mindfulness practice. This study aims at looking the relationship between parenting and the parents 'mindfulness practice on teenagers' emotional maturity behavior. This research utilized quantitative method using descriptive analysis with collecting data by the questioner. The sampling method was done by proportionate stratified random sampling method with a sample of 89 teenagers at the Ekayana Serpong Temple, Tangerang, Banten. Based on the results of the hypothesis test with regression analysis of the parental value is Sig 0.003 <0.05, or Tarithmetic 3.010> ttable 1.98793. Therefore, it can be concluded that there is a relationship between parenting on the emotional maturity behavior of teenagers. Hypothesis test results on parents 'mindfulness practices are Sig 0.000 <0.05, or t arithmetic 3,988> ttable 1.98793, these show that there is a correlation between parents' mindfulness practices on the emotional maturity behavior of teenagers. Based on the results of the hypothesis test, it is known that the significance value for the influence of parenting and parents' value is 43.189> F table 3.10. Thus, it can be concluded that there is an influence of parenting and parents 'mindfulness practices simultaneously towards emotional maturity behavior of teenagers, amounting to 50.1%, which means there is a positive influence between parenting and parents' mindfulness practices on emotional maturity behavior of teenagers. The results contribute to valuable knowledge for parents to be aware of better parenting patterns and the importance of practicing mindfulness, especially to shaping the emotional maturity behavior of teenagers.